Negro participation in apprenticeship programs - Briggs, Vernon M., JR.; Marshall, F. Ray; Texas Univ., Austin ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
Approaches and methods which have succeeded in increasing negro participation in selected apprenticeship programs were studied in order to recommend policies which would make it possible for negroes to further increase their participation in and successful completion of apprenticeship programs. Interviews in 10 major cities with 121 officials concerned with negro participation and 127 negroes involved directly in apprenticeship programs provided a valuable understanding of the depth and scope of the complex problem. The limited number of negro apprentices is due to a complex constellation of factors which are deeply embedded in the total American society. Negro youngsters do not have an equal chance of learning about apprenticeship training, of being motivated to try to enter these programs, of meeting the qualifications, of passing the tests, or of successfully completing these programs. Many of the objective standards of apprentice selection are racially motivated and if a supply of qualified applicants is generated and continues to be barred from apprentice programs, public policy might have to devote more attention to the qualifications and testing procedures used to select trainees. Two of the most important policies needed to increase negro participation are measures that would improve the quality of education available to disadvantaged youth and policies to maintain full employment and economic growth. The municipal, federal, civil rights, industry, union, and state officials all have important roles to play in increasing the number of negro apprentices. (hc)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Apprenticeships; Black Employment; Black Youth; Blacks; Community Action; Disadvantaged Youth; Educational Discrimination; Employment Opportunities; Interviews; Racial Discrimination; Unions